Maintaining the Values of a Profession: Institutional Work and Moral Emotions in the Emergency Department - Wright, April L.; Zammuto, Raymond F.; Liesch, Peter W. (Academy of Management Journal, 2017)
Specialization within professions creates challenges for maintaining the macro-level values of the profession in the everyday work of specialists at the micro level inside organizations. By conducting a qualitative study of emergency-department physicians and their interactions with other hospital specialists, we show how specialists maintain professional values through two distinct processes of institutional work in which moral emotions—that is, emotions linked to the interests of others—play a key role. The first process is activated when a perceived episodic problem, which arises from value conflicts in interactions between different specialists, elicits transitory moral emotions that motivate institutional maintenance work through individual action. The second process is activated when a perceived systemic problem, which arises from conflict between professional values writ large and organizational practices, elicits moral emotions that are enduring and shared across specialists. These emotions mobilize collective action in institutional maintenance work that changes the organizational practice. By focusing on values as a source of conflict and a motive for professional action inside organizations, our model contributes a nuanced understanding to the everyday work of professionals and specialists and draws attention to emotion elicitors and emotional scope as affective mechanisms in processes of institutional work.